2014
DOI: 10.1136/vr.102019
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen presence in feral pigs and their movement around two commercial piggeries in Queensland, Australia

Abstract: Feral pigs are wild animal reservoirs of infectious pathogens transmissible to other species, all of which are transmissible to domestic pigs. The objective of this study was to detect the presence of harmful production-limiting pathogens; Brucella suis, Leptospira species, Lawsonia intracellularis, Mycoplasma hyopneumoniae and Actinobacillus pleuropneumoniae in a feral pig population within a 10 km radius of two large-scale commercial piggeries in Southern Queensland, Australia. The movement pattern of six pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…In this regard, we already are testing kidneys collected from rodents trapped from several ecological sites, to establish the renal carriage of pathogenic Leptospira and genomic identity of Leptospira species carried by rodents in Uganda. In the present study, we found a high prevalence of anti-Leptospira antibodies against serovar Tarassovi, which has also been reported in cattle (18,23) and pigs (24,25) in East Africa and elsewhere. Though there are not many published reports of leptospirosis in other species of animals in Uganda, we still think that the nature of animal husbandry practices may facilitate interspecies interactions and spread of Leptospira infection.…”
Section: Discussionsupporting
confidence: 83%
“…In this regard, we already are testing kidneys collected from rodents trapped from several ecological sites, to establish the renal carriage of pathogenic Leptospira and genomic identity of Leptospira species carried by rodents in Uganda. In the present study, we found a high prevalence of anti-Leptospira antibodies against serovar Tarassovi, which has also been reported in cattle (18,23) and pigs (24,25) in East Africa and elsewhere. Though there are not many published reports of leptospirosis in other species of animals in Uganda, we still think that the nature of animal husbandry practices may facilitate interspecies interactions and spread of Leptospira infection.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, in a study in New South Wales, researchers found antibodies to L. interrogans serovar Pomona in 53% of 239 feral pigs surveyed [ 21 ]. Furthermore, a high seroreactivity rate (48.6%) to Leptospira species was found in feral pigs in Queensland, Australia [ 22 ]. It is not clear why pigs in our study had a higher seroprevalence than pigs in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…High detection rates of HEV (>20%) were reported in in Czeck Republic, France, Germany, Italy, Lithuania, Poland, Portugal and Spain (Anheyer-Behmenburg et al, 2017, Dorn-In et al, 2017, Jori et al, 2016, Kubankova et al, 2015, Mesquita et al, 2016, Montagnaro et al, 2015, Rivero-Juarez et al, 2018, Spancerniene et al, 2018. particularly at risk of inter-population transmission with wild boars because they belong to the same species and share the same community of potential pathogens (Pearson et al, 2014).…”
Section: Hepatitis E Virusmentioning
confidence: 99%